RANCANG BANGUN ALAT MIXER VERTIKAL ADONAN KUE DONAT DENGAN GEARBOX TIPE BEVEL GEAR KAPASITAS 7 KILOGRAM - Fadwah Maghfurah; Hendro Purwono; Windarta Windarta (Teknoin, 2016)
Making doughnut in a small-scale industry generally has a problem with inappropriate equipment and easy to be broken like using hand mixer. In its gearbox, the cylindrical worm gear usually made of plastic so that will easy to worn. With the use gearbox type bevel gear made of metal, then the mixer would able to overcome the problem of dough mixing where the gearbox of this type can overcome the large load with high rotation, so that the capacity of the mixer can be enlarged so that it will increase the results of work productivity. The design method begins with observation of the impact of performance, efficiency, needs and ergonomics and then proceed with the design concept of the tool design, calculation of the construction of the tool and its components and the last phase is testing of the tool by trial and error. Calculations were made to the components that will be assembling such as axis, pegs, bearings, bevel gear and its gear ratio, then the construction framework of the mixer and the container for the dough to be stirred. From the calculation results obtained from the capacity of the hand mixer with the use of 7 kg / hour, the bevel gear mixer can improve productivity results with a larger capacity of 18 kg / hour or increased by 225% compared to hand mixer capacity.